# 6s^2-13s+6=

## Simple and best practice solution for 6s^2-13s+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6s^2-13s+6= equation:

Simplifying
6s2 + -13s + 6 = 0

Reorder the terms:
6 + -13s + 6s2 = 0

Solving
6 + -13s + 6s2 = 0

Solving for variable 's'.

Factor a trinomial.
(2 + -3s)(3 + -2s) = 0

Subproblem 1Set the factor '(2 + -3s)' equal to zero and attempt to solve:

Simplifying
2 + -3s = 0

Solving
2 + -3s = 0

Move all terms containing s to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -3s = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -3s = 0 + -2
-3s = 0 + -2

Combine like terms: 0 + -2 = -2
-3s = -2

Divide each side by '-3'.
s = 0.6666666667

Simplifying
s = 0.6666666667
Subproblem 2Set the factor '(3 + -2s)' equal to zero and attempt to solve:

Simplifying
3 + -2s = 0

Solving
3 + -2s = 0

Move all terms containing s to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2s = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -2s = 0 + -3
-2s = 0 + -3

Combine like terms: 0 + -3 = -3
-2s = -3

Divide each side by '-2'.
s = 1.5

Simplifying
s = 1.5Solutions = {0.6666666667, 1.5}`